Signal averaged laser Doppler measurements of activation–flow coupling in the rat forepaw somatosensory cortex - Detre, John A; Ances, Beau M; Takahashi, Kazushi; Greenberg, Joel H (Brain research, 1998)
Regional alterations in cerebral blood flow (CBF) are widely used as a surrogate for neuronal function based on an intact coupling between changes in regional CBF and metabolism, activation–flow coupling (AFC). To further investigate parameters affecting AFC, we have implemented a rat model with electrical forepaw stimulation under α-chloralose anesthesia using laser Doppler (LD) measurements of flow parameters through thinned skull over contralateral somatosensory cortex. Signal averaging of the LD response was used to improve reproducibility. A characteristic flow response to electrical forepaw stimulation was reliably recorded from the somatosensory cortex using signal averaging. Stimulation at 5 Hz maximized the LD response, and constant current stimulation up to 1 mA did not induce changes in systemic blood pressure. The shape of the flow response consisted of an initial peak followed by a steady state plateau phase which was observed for stimulation durations longer than 4 s. When individual LD parameters of velocity, red blood cell concentration (CRBC), and cerebral blood flow (CBF) were compared, changes in LD CBF were primarily attributable to changes in LD velocity rather than LD CRBC. This finding was also observed during hypercapnia. Characterization of AFC in the model provides a background for future studies of the effects of pharmacological manipulation or pathophysiological states.